DNA repair deficiency as circulating biomarker in prostate cancer - Catalano, Martina; Generali, Daniele; Gatti, Marta; Riboli, Barbara; Paganini, Leda; Nesi, Gabriella; Roviello, Giandomenico (Frontiers in Oncology, 2023)
Deleterious aberrations in DNA repair genes are actionable in approximately 25% of metastatic castration-resistant prostate cancers (mCRPC) patients. Homology recombination repair (HRR) is the DNA damage repair (DDR) mechanism most frequently altered in prostate cancer; of note BRCA2 is the most frequently altered DDR gene in this tumor. Poly ADP-ribose polymerase inhibitors showed antitumor activity with a improvement in overall survival in mCRPC carrying somatic and/or germline alterations of HHR. Germline mutations are tested on peripheral blood samples using DNA extracted from peripheral blood leukocytes, while the somatic alterations are assessed by extracting DNA from a tumor tissue sample. However, each of these genetic tests have some limitations: the somatic tests are related to the sample availability and tumor heterogeneity, while the germline testing are mainly related to the inability to detect somatic HRR mutations. Therefore, the liquid biopsy, a non-invasive and easily repeatable test compared to tissue test, could identified somatic mutation detected on the circulating tumor DNA (ctDNA) extracted from a plasma. This approach should better represent the heterogeneity of the tumor compared to the primary biopsy and maybe helpful in monitoring the onset of potential mutations involved in treatment resistance. Furthermore, ctDNA may inform about timing and potential cooperation of multiple driver genes aberration guiding the treatment options in patients with mCRPC. However, the clinical use of ctDNA test in prostate cancer compared to blood and tissue testing are currently very limited. In this review, we summarize the current therapeutic indications in prostate cancer patients with DDR deficiency, the recommendation for germline and somatic-genomic testing in advanced PC and the advantages of the use liquid biopsy in clinical routine for mCRPC.